Hilbert scheme of points on cyclic quotient singularities of type (p, 1) - Gyenge, A (Springer Nature, 2016)
In this note we investigate the generating series of the Euler characteristics of the Hilbert scheme of points on cyclic quotient singularities of type (p, 1). We link the appearing combinatorics to p-fountains, a generalization of the notion of fountain of coins. We obtain a representation of the generating series as a coefficient of a two variable generating series.